2019
DOI: 10.1108/aam-05-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding cultural projects and networking the value creation

Abstract: Purpose The purpose of this paper is to investigate how online crowdfunding is strategically applied to artistic productions featuring strong social and cultural values, exploring potential and risks of networking value creation and community engagement. Mission-driven initiatives and their crowdfunding campaigns are analyzed through platform society framework (van Dijk, 2019), considering the business models and marketing strategies that support the scope and intentions of a variety of agents involved within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Until 2019, PPL accepted user log-ins through the Facebook API. However, after becoming the target of suspicion and undergoing an audit by governmental regulators due to controversial campaigns like the "Nurses' strike" (Foá, 2019), it adapted its user registration policy and personnel data gathering practices.…”
Section: Onboardmentioning
confidence: 99%
“…Until 2019, PPL accepted user log-ins through the Facebook API. However, after becoming the target of suspicion and undergoing an audit by governmental regulators due to controversial campaigns like the "Nurses' strike" (Foá, 2019), it adapted its user registration policy and personnel data gathering practices.…”
Section: Onboardmentioning
confidence: 99%
“…By sharing their experiences at heritage sites, posting photos and videos, and engaging in discussions, participants contribute to preserving cultural heritage by raising awareness and encouraging others to engage with it (Psomadaki et al, 2019). People can also make donations through social media, sign up for volunteer programs, and participate in events that preserve heritage sites (Beel et al, 2017;Foa, 2019). This level of participation has helped create a sense of community among heritage supporters and forges a deeper connection with heritage (Cotterill et al, 2016).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The literature review has identified the directions of the research conducted so far on the value created in CF. Although the topic of value creation in CF is taken up by re-searchers, it mainly concerns projects of a social or cultural nature [19,19,20,[77][78][79][80][81]; there is little research conducted only on the financing of typical business projects. The current research is mainly theoretical or in the form of case studies and, as such, is insufficient to draw practical conclusions related to the management and value creation of business projects in CF.…”
Section: Literature Review-the Value In Cfmentioning
confidence: 99%